Protection Against Malaria by Intravenous Immunization with a Nonreplicating Sporozoite Vaccine - Seder, Robert A.; Chang, Lee-Jah; Enama, Mary E.; Zephir, Kathryn L.; Sarwar, Uzma N.; Gordon, Ingelise J.; Holman, LaSonji A.; James, Eric R.; Billingsley, Peter F.; Gunasekera, Anusha; Richman, Adam; Chakravarty, Sumana; et al. (Science (American Association for the Advancement of Science), 2013)
Consistent high-level, vaccine-induced protection against human malaria has only been achieved by inoculation of Plasmodium falciparum (Pf) sporozoites (SPZ) by mosquito bites. We report that the PfSPZ Vaccine—composed of attenuated, aseptic, purified, cryopreserved PfSPZ—was safe and well tolerated when administered four to six times intravenously (IV) to 40 adults. Zero of six subjects receiving five doses and three of nine subjects receiving four doses of 1.35 × 10⁵ PfSPZ Vaccine and five of six nonvaccinated controls developed malaria after controlled human malaria infection (P = 0.015 in the five-dose group and P = 0.028 for overall, both versus controls). PfSPZ-specific antibody and T cell responses were dose-dependent. These data indicate that there is a dose-dependent immunological threshold for establishing high-level protection against malaria that can be achieved with IV administration of a vaccine that is safe and meets regulatory standards.